Iknô kãtô, Ĩsitro nã akwe krsakrtamnõze dasĩpsêwa Kãtô kmã psêkwaĩnõrĩ, Danõhikwa – a corrida de toras curtas e longas entre o povo Akwẽ Xerente no Dasἶpê-festa cultural - Xerente, Afonso Tiikwa (2020)
My work tells how are log races among the Akwẽ, and brings some comparison with studies done by authors, great anthropology researchers about log races and about ritual that happen during Dasipe, the great nomination ritual developed in the villages. I think that this dissertation is, in a certain way, an indigenous anthropology about my people Akwẽ-Xerente. I also speak about clan associations, respect among clans, specific treatment language, how is sustainability today and in the old days. I bring a Kupre description, a very strong Akwẽ- Xerente ceremony. It does not happen during Dasipe, but after an elder death; at the time, they make another painting, six clans that form two groups, two lines with the same clan moiety, as for example, Kritodtekwa with Kbazidtekwa and Kuzapdtekwa, a line with the same moiety, and the other is Kraiprehidtekwa with Krozakedtekua and Wahiredtekwa, another moiety. Marriage also happens away from Dasipe, and it can happen during the cultural feast which is also a very strong ceremony made by the girl´s uncles. I do also a descrition of children´s log races, adults with a short log, and big log race, in which adult men run such logs by the end of the cultural feast, closing Dasipe.